Patient-Centered Neurosurgery: Improved Outcomes after Subtotal Surgical Resection and Nonframe-Based Fractionated Stereotactic Radiotherapy for Large Cerebellopontine Angle Vestibular Schwannoma - Darpanarayan Hazra; Gina Maryann Chandy; Sanjoy Roy; Amit Ghosh (Indian Journal of Neurosurgery)
Background The novel paradigm in neurosurgery for large vestibular schwannomas (VSs) involves a combination of planned subtotal resection (STR) and scheduled postoperative fractionated stereotactic radiotherapy (FSRT).